Assessment of the profitability and productivity of Jute-T Aman-Maize cropping pattern at char land in Jamalpur district of Bangladesh: Profitability of cropping pattern at char land (SAARC Journal of Agriculture, 2022)
People living in the char land area are considered the most disadvantaged group of people in Bangladesh. Considering the situation, a study was conducted to evaluate the feasibility of increasing income of char dwellers by following profitable cropping pattern. The treatments were CP1 (Farmers’ practice cropping pattern): Grass pea (BARI Khesari- 1)-Jute (var. JRO 524)-T. Aman (var. Swarna) and CP2 (Altered cropping pattern): Maize (var. Hybrid 981)-Jute (var. JRO 524)-T. Aman (var. Binadhan-11). A randomized complete block design with six dispersed replications was followed in this experiment. It was observed that the altered cropping pattern (CP2) produced higher rice equivalent yield (avg. 25.47 t ha-1), production efficiency (78.61 kgha-1 day-1) and gross margin US$ 3056.58 ha-1 than those of the farmer’s practice cropping pattern (CP1) rice equivalent yield (12.97 t ha-1), production efficiency (40.40 kgha-1 day- 1) and gross margin (Tk. 79,950 ha-1). Gross margin increased by 206% in altered cropping pattern compared with the existing cropping pattern, revealing that rabi crop based cropping pattern including flood damage escaping rice varieties {Maize (var. Hybrid 981)-Jute (var. JRO 524)-T. Aman (var. Binadhan-11)} is appropriate for getting higher productivity and profitability by the poor char dwellers of Jamalpur district in Bangladesh.SAARC J. Agric., 20(2): 121-131 (2022)